(untitled) (Research, Society and Development, 2020)
This paper presents part of the results of a research developed with a first year High School class of a public school, located in the urban area of Caçapava do Sul, RS. In its execution, the Problem Solving methodology was used, starting from the research question: “How to enhance the learning in the Chemistry discipline, through the use of the Problem Solving methodology?” Seeking, thus, the improvement of the teaching and learning and better understanding of the content involved. Problem solving strategies were employed to encourage reading, research, collective construction of knowledge and explanation of results obtained. Qualitative research was used, the data were produced by reflections in logbook, reading reports and transcription of audios of the classes in which the work was implemented. The analysis of the results was performed according to the Bardin Content Analysis methodology. From this research, it was evidenced some difficulties of the students in the aspects related to the different stages of the implementation of the proposal and revealed potentialities of the use of Problem Solving, such as the development of cognitive skills during the elaboration of strategies, motivation, reflection. criticism, creativity and argumentation.